Local application of biphosphonate as a biochemical barrier against bone graft resorption in mandibular reconstruction - Romzi Hanif; Cahya Y. Hasan; Muhammad M. Rahmat; Rahardjo (DiscoverSys Inc., 2021)
Objective: This paper was aimed at examining the positive results of iliac bone graft osteogenesis and osteointegration following the local application of bisphosphonate in mandibular reconstruction. Methods: A 22-years-old female patient came with a complaint of pain-free right cheek mass that has enlarged slowly since 2 years. Radiographic examination shows cloudy radiolucent images in the right mandibular corpus to the right mandibular ramus, while histopathological examination indicates ossifying fibroma. Patient underwent mandibular resection followed by iliac bone graft-based mandibular reconstruction. Bone graft was immersed with bisphosphonate (zoledronate acid 0.005 mg /ml) for 3 minutes, then rinsed with saline in 3 minutes, followed by fixing bone graft on the reconstruction plate.Results: Postoperative follow up in the 36th week showed no signs of infection and dehiscence in the surgery site, and the radiographic examination indicated signs of osteogenesis and osteointegration of mandibular bone graft.Conclusion: Local application of biphosponate on bone graft promotes the favorable results of osteogenesis and osteointegration in mandibular reconstruction.